Influence of particle size on the photoactivity of Ti/TiO2 thin film electrodes, and enhanced photoelectrocatalytic degradation of indigo carmine dye - Guaraldo, T. T. [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V. Sa, 2011)
Photoanodes based on Ti/TiO2 thin films were prepared by the sol-gel method, using either tetraisopropoxide (Ti(OPri)(4)) or modified tetraisopropoxide, producing electrodes with different sized nanoparticle coatings, termed nanoporous (20 nm) or nanoparticulated (10 nm) electrodes. The anatase form dominated the composition of the nanoparticulated electrode, which presented a higher surface area, a fiat band potential shift of -160 mV and a 50% improvement in photoactivity, compared to the nanoporous electrode. 100% color removal, and 75% mineralization, of indigo carmine dye were achieved after 15 min of photoelectrocatalytic treatment using a nanoparticulated Ti/TiO2 electrode operated at a current density of 0.4 mA cm(-2). Our findings indicate that the use of nanoparticulated electrodes, under UV irradiation and with controlled current density, is an efficient alternative for the removal of food dye contaminants during wastewater treatment. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Indigo carmine; Photoelectrocatalytic treatment; Nanoporous TiO2; Nanoparticulated TiO2; Thin films; Sol-gel